Effects of Stormwater Pipe Size and Rainfall on Sediment and Nutrients Delivered to a Coastal Bayou. (1st September 2015) - Grigas, Daniel; Lehrter, John; Cebrian, Just; Chen, Yushun; Ehmen, Brenna; Woodrey, Mark
ABSTRACT: : Pollutants discharged from stormwater pipes can cause water quality and ecosystem problems in coastal bayous. A study was conducted to characterize sediment and nutrients discharged by small and large (< 20 cm and >20 cm in internal diameters, respectively) pipes under different rainfall intensities (< 2.54 cm and > 2.54 cm, respectively). Results showed that large pipes had greater discharge than small pipes. Pollutants concentrations did not vary by pipe size. Large pipes had greater loads of TSS (138.2 vs. 24.0 mg/s), NO3 − (5.54 vs. 2.74 mg/s), and NH4 + (0.39 vs. 0.19 mg/s) than small pipes. Neither discharge nor constituents varied by rainfall events. Pipe size may be a useful metric for estimating loads to a system. Nutrient reduction efforts should be directed to reducing the dissolved nutrient pools, while stormwater management efforts should be directed to reducing pipe freshwater discharge volumes that drive constituent loads.